The modernity of the research of Romanian astronomer Constantin Popovici - Chiruta, C. (Advances in Astronomy and Space Physics, 2011)
We present the model of the photogravitational field proposed by the romanian mathematician Constantin Popovici, basic equations. We give the variation of orbital energy in the photogravitational two bodies problem and energy integral. In this case the orbital energy is not conserved.